Use of exercise Doppler for non-invasive haemodynamic optimization of dose and identification of poor responders to an oral anti-anginal agent. A double-blind dose-finding study of nisoldipine. Issue 756 (October 1988) - Singer, M.; Trotman, I. F.
Abstract : Nisoldipine, a new dihydropyridine calcium antagonist, was examined for its dose-related haemodynamic effects using exercise-induced changes in aortic blood flow as measured by Doppler ultrasound. Following a two-week placebo run-in, 24 patients with stable angina pectoris were assigned double-blind to one of three groups receiving doses ranging from 2.5-20 mg/day over 8 weeks, given once or twice daily. Doppler studies identified the low dose group as responding less well at the placebo phase compared to the other two groups. There was an overall improvement in percentage change of peak velocity and stroke distance with exercise at all doses, with a dose of 5 mg/day giving optimal benefit in both variables (P less than 0.05) and no additional benefit being seen on twice-daily dosage. Six patients reporting increased chest pain exhibited a significantly worse rise in peak velocity and a fall in stroke distance to exercise (P less than 0.05) whilst on active drug compared to those who responded favourably. Doppler ultrasound can be of benefit in the haemodynamic assessment of new drugs, the recognition of non-responders and the optimization of therapeutic regimes.